USING WALNUT SHELLS AS FUEL - TSURKAN, OLEH; SPIRIN, ANATOLII; RUTKEVYCH, VOLODYMYR; DIDYK, ANDRII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
With the complete processing of walnuts, in addition to the main product - the kernel of the walnut, its shell remains. The technology of processing walnuts involves the presence of a drying process, which is the most energy-consuming for the entire technology. The most common modern convective dryers in agriculture consume 5.5 – 6.0 MJ/kg of evaporated moisture. In today's conditions, with a significant shortage of traditional energy sources, it is advisable to turn to alternative fuels, one of which is walnut shells. It has a high calorific value (21 MJ/kg) and low ash content.The analysis of recent studies and publications indicates that the problem of using plant residues as fuel is being developed by domestic and foreign researchers. The main attention is paid to the waste of the main crops grown in Ukraine: wheat, corn for grain and sunflower. The use of waste as fuel requires specific conditions for the organization of the combustion process, the operation of fuel combustion plants and the arrangement of combustion product purification systems. An analysis of recent studies shows that the question of the theory and practice of walnut shell combustion remains open. The focus is on "traditional" fuels from plant residues.The aim of the research is to reduce energy expenditure in the processing of walnuts by developing theoretical and practical measures and means for the use of nutshells as fuel. From an energy point of view, walnut shells are on a par with traditional fuels, which are used, among other things, in agriculture. After all, the heat of combustion of walnut fuel briquettes is about 21 MJ/kg, and with a very low ash content (about 1%). For comparison: the calorific value of equivalent fuel is 29.35 MJ/kg, natural gas 33-38 MJ/m3, lignite on average 24 MJ/kg, wood 10-12 MJ/kg.
Keywords: walnut shell; specific heat of combustion; physical and mechanical properties of walnut; combustion rate; excess air coefficient; boiler